Influential Factors on English E-Learning Behavioral Intention and Usage Among Undergraduates at Chengdu University, Sichuan, China - Wang, Shuhui (Scholar: Human Sciences, 2025)
Purpose: The research investigates factors impacting the E-learning Behavioral Intention and Use behavior of undergraduates in non-English majors of Chengdu University who represent the undergraduates of Sichuan Province in China. Research design, data, and methodology: 496 sample data from the target group was gathered using a questionnaire and the quantitative approach. After the index of item-objective congruence (IOC), and Cronbach's Alpha, the Confirmatory factor analysis (CFA) was applied to test the data to verify the causal link between the variables and the model's goodness of fit. Finally, the Structural Equation Model (SEM) was again applied to conclude the impact strength of each variable. Results: All six hypotheses are supported at the p-value ranging from, showing a significant impact. The impact strengths of the factors are in the order of behavioral intention to use behavior, hedonic motivation to behavioral intention, self- efficacy to behavioral intention, effort expectancy to behavioral intention, facilitating conditions to use behavior, and performance expectancy to behavioral intention. Conclusions: In order to spread English E-learning among undergraduates in China, governments, university administrators, and English E-learning cooperating companies should pay full attention to the impacting factors investigated in this research and follow up policies and measurements to create a comfortable English E-learning setting.